Information in crisis: Health & technology‐related information behaviors of parents in emergency departments. Issue 1 (27th December 2016) - Given, Lisa M.; Willson, Rebekah; Albrecht, Lauren; Scott, Shannon D.
ABSTRACT: This research examined the information behavior of parents (including legal guardians) during an emergent health situation with a child. Although many studies examine health‐related information behaviors, very few explore health consumers' information practices during moments of health crisis. This study explored parents' information needs, source use, and source preferences during a visit to the emergency department. An online questionnaire was administered using iPads given to 897 parents with children at one of 32 participating general emergency departments (ED) across Canada. Before taking their child to the ED, only 38.8% (n=348) of parents looked for information; those who did search looked most frequently for information about specific symptoms or severity of illness. Prior to visiting the ED the sources most frequently accessed were the internet and direct contact with healthcare professionals. At the emergency department, parents' information needs centred on immediate concerns, including explanations of their child's illness, treatments, and care instructions. Household income, education level, and parents' age were factors that affected information seeking in emergent health situations. Overwhelmingly, speaking to a healthcare professional in person is the typical and preferred way to obtain health information when facing a health crisis involving a child. The results have implications for how and when healthcare information is shared; the findings add to the limited research on parents' information behavior, particularly their roles as information proxies for their children.